DOPPLER EVALUATION OF UMBILICAL ARTERY FLOW PATTERN IN ANEMIC PREGNANT WOMEN (The Research of Medical Science Review, 2025)
Objective: To evaluate umbilical artery doppler indices in anemic pregnant women for reducing adverse effects of anemia on maternal and fetal health.The study aims to contribute to the understanding of how anemia and other forms of anemia affect pregnancy outcomes, particularly in the context of placental function. Additionally, the study seeks to assess the predictive value of Doppler velocimetry in this setting, providing valuable insights into its potential role in the early detection of complications Study design: It was a Descriptive cross-sectional study design. Place and duration of study: The study was conducted at THQ Hospital Pattoki, Pakistan from August to December 2024. Material and Methods: This study follows a descriptive, cross-sectional research design, which is appropriate for evaluating and analyzing the umbilical artery flow patterns in pregnant women diagnosed with anemia at a particular point in time. The study design aims to describe the relationship between anemia severity and Doppler ultrasound findings in pregnant women and evaluate the prevalence of abnormal flow patterns in the umbilical artery. Results: The study involved 72 anemic pregnant women with a mean gestational age of 26.44 weeks (SD = 4.82), indicating mid-pregnancy. The average Body Mass Index (BMI) was 26.39 (SD = 1.62), suggesting that most participants were slightly overweight. Hemoglobin levels averaged 10.29 g/dL (SD = 1.21), reflecting mild anemia, with values ranging from 7.8 to 12.9 g/dL. In terms of Doppler ultrasound parameters, 65.3% of participants (47 cases) had a normal systolic/diastolic (S/D) ratio, indicating stable placental perfusion. However, 26.4% (19 cases) showed moderate abnormalities, and 8.3% (6 cases) exhibited severe abnormalities. Regarding the Resistance Index (RI), 70.8% (51 cases) had normal values, suggesting good vascular conditions, while 27.8% (20 cases) showed moderate changes, and 1.4% (1 case) had severe abnormalities. For the Pulsatility Index (PI), 41.7% (30 cases) of participants had normal values, while 48.6% (35 cases) showed moderate changes, and 9.7% (7 cases) had severe abnormalities, indicating a need for clinical intervention in some cases. Crosstab analysis revealed that a majority of participants with mild and moderate anemia had normal RI values, with 21 cases each in the mild and moderate anemia categories showing normal RI. However, the chi-square test revealed no significant association between hemoglobin levels and RI categories (p=0.434p = 0.434p=0.434). Similarly, for the S/D ratio, 65.3% of mild and moderate anemia cases exhibited normal values, but no significant association was found between hemoglobin levels and S/D ratio (p=0.281p = 0.281p=0.281). Likewise, in the case of PI, moderate PI abnormalities were most common among those with mild and moderate anemia, but again, no significant correlation between hemoglobin levels and PI was observed (p=0.157p = 0.157p=0.157). Regarding maternal weight, 50% (36 cases) of participants were of normal weight, 20% (14 cases) were underweight, and 10% (7 cases) were overweight. The results underscore the clinical significance of monitoring Doppler parameters in anemic pregnant women, as Doppler abnormalities were more prevalent despite the absence of significant statistical associations. These findings suggest the need for further research with larger sample sizes to explore potential causal relationships and refine management strategies for anemia in pregnancy, emphasizing the importance of clinical observation in managing placental perfusion and maternal-fetal health. Conclusion:This study provides valuable insights into the Doppler evaluation of umbilical artery flow patterns in anemic pregnant women. The findings suggest that while many participants exhibited normal Doppler parameters, such as the systolic/diastolic (S/D) ratio and resistance index (RI), a significant portion of the sample demonstrated moderate pulsatility index (PI) abnormalities, indicating a potential compromise in placental perfusion. Despite the prevalence of mild and moderate anemia, the chi-square analysis revealed no significant association between hemoglobin levels and Doppler parameters, highlighting the complexity of anemia in pregnancy. This lack of significant correlation suggests that other factors, aside from hemoglobin levels, may contribute to abnormal Doppler findings. Additionally, the study underscores the importance of continued clinical observation and the need for further investigation into the mechanisms behind Doppler abnormalities in anemic pregnancies. Larger sample sizes and more in-depth studies are needed to better understand the relationship between anemia, placental perfusion, and fetal outcomes. Overall, the study emphasizes the clinical importance of Doppler assessments as a tool for monitoring placental health in pregnant women with anemia, and advocates for further research to improve the diagnosis and management of anemia in pregnancy to enhance maternal and fetal health outcomes.